Occupational health: is there a place for nutrition promotion programs? - Costa, Vânia (2019)
Occupational health is also responsible for valuing the workplace, as a privileged setting for health promotion and healthy lifestyles of employees. The implementation of workplace nutrition programs aims to promote healthier eating habits and increase nutritional literacy, with the vision of employees with a lower rate of absenteeism, healthier and more motivated. This action research project pretends to describe the implementation of a workplace nutritional promotion program in the context of occupational health. Since February 2017 was developed a nutrition action research project with a nutritional support program implementation to 443 employees. This program comprises 4 dimensions: 1) Nutrition Counseling - in multidisciplinary articulation with occupational health, psychology, and medicine; 2) Workplace environment changes - intervention on the menus, food portions, nutritional and food quality; 3) Nutrition education and literacy – workshops and publications; 4) Other activities group-focused - promotion of fruit and vegetables, nutritional counseling for salt reduction, counseling for focus group- drivers). To target our interventions, the project had the first phase for self-reported data collection (anthropometric measurements, food habits and satisfaction with the canteen menu and food supply on the bar and canteen). In the second phase, we designed focus-interventions and collected data from each intervention. In the first phase, we collected data from 320 employees predominantly male (60.9%) with 47±10 years. 47.0% of workers reported to have a disease diagnosed by the doctor and 27.0% reported to perceive to have a reasonable or weak health. According to BMI, 40.3% were overweight and 15.3% were obese, and the male had higher BMI (U=6931.5; p=0.000). About the satisfaction with canteen menu and food supply on the bar and canteen, 31.5% (n=101) of the workers made suggestions for the canteen menus such as improve the variety of options in the menu, improve the variety of vegetable/salads on the meal, have a vegetarian option, decrease the fried foods and increase fish options. A proposal was made to the company managers considering the nutrition balance and employees' opinions, and its implementation is ongoing. We also evaluated the fruits and vegetable intake. We concluded that 58.8% of employees' fruit intake is below recommendations. The company started the “1 fruit per day” program, which provides fruit weekly to all workers. The 6 months program evaluation is ongoing. In the first 6 months, we had a nutrition counseling adhesion of 44 workers and 50% maintain follow-up after 2 years. The main reason for nutrition counseling was excessive weight (72.7%). In the first 6 months period, 50% had weight loss average of 1.7kg, 63.6% improved their food habits and 18.2% started weekly physical activity. Were organized 3 workshops for nutrition education: “Food labeling”, “How to reduce salt in the diet” and “Healthy homemade lunches brought to the workplace”. We implemented knowledge pre-assessment and a final evaluation of acquired competences. Using a Likert scale of 1-5 for employees acquired competences perception, we obtain an average classification of 4.4. This is an ongoing project but we identify workers’ motivation, participation in the program and valorization of initiatives to adopt a healthy lifestyle. Employees and companies can benefit from these projects.